A regularização fundiária urbana na Lei 13.465/17: análise de retrocessos e rupturas face a função social da propriedade na CF/88 - Petry, Franciéle (2023)
The research questioned whether Law No. 13,465/17, when regulating urban land regularization, was characterized as a setback compared to full land regularization, previously presented by Law No. 11,977/09 and, consequently, whether it represented a break in the constitutional paradigm of the right to property, centered on the idea of ​​social function and the right to the city. The right to property, being a fundamental right, had dynamic characteristics, following the political, legal and social evolution of the State. Thus, in the Liberal State it was presented as an individual and patrimonial right. In the Social State, it added socializing elements, with property characterized by its multiple functions - social, environmental, economic - and by the development of the city's social functions. In a context of exacerbated urbanization and inequality, as well as housing shortages, Brazilian urban development was independent of urban planning norms, with numerous informal urban centers emerging, in which segregation and precariousness of public services and equipment were observed. Based on the constitutional paradigms of the social function of property and cities, Law 11,977/2009 provided for full land regularization, based on a democratic process, which covered broad legal, urban, environmental and social regularization conducts, aiming at a multidisciplinary intervention in the consolidated urban reality. The Alternation of power, intrinsic to Brazilian political pluralism, sometimes caused instability and discontinuity in public policies. The supervening of Law 13,465/2017, repealing the previous legislation, presented a new urban land regularization policy with greater affinity to the economic function of property, promoting registration regularity (regularization-titling) to the detriment of broad regularization. Thus, Law 13,465/2017 represented a normative step backwards and a break with the constitutional paradigm, which established the social function of property and cities. Considering the normative possibilities and the need for social advancement, regularization-titles could be used as the first act, integrating the informal urban nucleus into the legal and formal city, giving strength and visibility to popular demands, without exempting the public authorities from promoting regularization full, which remains possible, based on the set of principles extracted from the Federal Constitution and City Statute. The proposed study had as its operational logic the deductive method and the qualitative approach. In terms of nature, it is basic research; In relation to the objectives, the research was exploratory and, with regard to the method of procedure, the monograph was used.